PENGARUH MOTIVASI KERJA DAN KOMPETENSI PROFESIONALTERHADAP KINERJA GURU SEKOLAH DASAR DI KECAMATAN CIKARANG UTARA, KABUPATEN BEKASI - Sumarsih, Sumarsih (JURNAL PENDIDIKAN DASAR, 2016)
Abstract: The objective of this research was to explaine the effect of work motivation and professional competency to job performance of the teachers at primary school in South Cikarang, Bekasi Regency. The research was conducted using survey method and quantitatif approach. Target population of this research as 462 teachers. Research samples were selected using simple random sampling technique as much as 214 teachers. The data were collected through questionnaires and competency test. The data were analyzed using path analysis techniques. Based on the results of this research concluded that: (1) the work motivation have positive direct effect to job performance, improvement of work motivation will lead to increased job performance; (2) the professional competency have positive direct effect to job performance, improvement of professional competency will lead to increased job performance; (3) the professional competency have positive direct effect to work motivation, improvement of professional competency will lead to increased work motivation. The job performance of the teachers can be improved by improvement work motivation and professional competency.Keywords: job performance, work motivation, professional competencyAbstrak: Tujuan dari penelitian ini adalah untuk menjelaskan pengaruh motivasi kerja dan kompetensi profesional dengan kinerja guru di sekolah dasar di Cikarang Utara, Kabupaten Bekasi. Penelitian dilakukan dengan metode survei dan pendekatan kuantitatif. Populasi target penelitian ini sebagai 462 guru. Sampel penelitian dipilih dengan menggunakan teknik simple random sampling sebanyak 214 guru. Data dikumpulkan melalui kuesioner uji kompetensi guru. Data dianalisis dengan menggunakan teknik analisis jalur. Berdasarkan hasil penelitian ini menyimpulkan bahwa: (1) motivasi kerja berpengaruh langsung positif terhadap kinerja pekerjaan, peningkatan motivasi kerja akan menyebabkan kinerja pekerjaan meningkat; (2) kompetensi profesional berpengaruh langsung positif terhadap kinerja pekerjaan, peningkatan kompetensi profesional akan mengakibatkan prestasi kerja meningkat; (3) kompetensi profesional berpengaruh langsung positif terhadap motivasi kerja, peningkatan kompetensi profesional akan menyebabkan motivasi kerja meningkat. Kinerja pekerjaan guru dapat ditingkatkan dengan motivasi kerja perbaikan dan kompetensi profesional.Kata kunci: Kinerja Guru, Motivasi Kerja, Kompetensi Profesional